Report of the Signal Transduction Society meeting 2018 - Signaling: from past to future - Schirmer, Bastian; Giehl, Klaudia; Hieke-Kubatzky, Katharina (International journal of molecular sciences, 2019)
The annual meeting “Signal Transduction—Receptors, Mediators, and Genes” of the Signal Transduction Society (STS) is an interdisciplinary conference open to all scientists sharing the common interest in elucidating signaling pathways in physiological or pathological processes in humans, animals, plants, fungi, prokaryotes, and protists. On the occasion of the 20th anniversary of the STS, the 22nd joint meeting took place in Weimar from 5-7 November 2018. With the focus topic “Signaling: From Past to Future” the evolution of the multifaceted research concerning signal transduction since foundation of the society was highlighted. Invited keynote speakers introduced the respective workshop topics and were followed by numerous speakers selected from the submitted abstracts. All presentations were lively discussed during the workshops. Here, we provide a concise summary of the various workshops and further aspects of the scientific program.